Evaluation of the pharmacokinetics and efficacy of transdermal flunixin for pain mitigation following castration in goats. Issue 4 (30th October 2020) - Graves, Meggan T; Schneider, Liesel; Cox, Sherry; Caldwell, Marc; Krawczel, Peter; Lee, Amanda; Lear, Andrea
Abstract: The mitigation of pain associated with common management procedures is a rising concern among veterinarians, producers and consumers. Nonsteroidal anti-inflammatory drugs are vital compounds for this purpose due to their cost, convenience, and efficacy. A transdermal formulation of flunixin meglumine (FM) was approved for the treatment of pain in cattle; however, the efficacy has yet to be determined for small ruminants. The current study had two aims: 1) to determine the pharmacokinetics of transdermal flunixin meglumine (TD FM) in bucklings and 2) to evaluate pain mitigation by TD FM following castration. To evaluate pharmacokinetics, 12 male goats (mean age = 6 mo) received 2.2 mg/kg of FM IV ( n = 6) or 3.3 mg/kg TD FM ( n = 6). Plasma FM concentrations were measured. The mean C max, T max, and harmonic mean half-life for TD FM were 1.09 ± 0.65 μg/mL, 5.50 ± 2.95 h, and 7.16 ± 2.06 h, respectively. To evaluate the efficacy of pain mitigation, 18 goats were randomly assigned to three treatment groups: 1) TD FM and castration (FM CAST) ( n = 6); 2) transdermal placebo and castration (PL CAST) ( n = 6); and 3) TD FM and sham castration (SHAM) ( n = 6). Plasma samples were collected at 0, 12, 24, 36, 48, 72, and 96 h to assess cortisol and prostaglandin E2 (PGE2 ). Daily dry matter intake (DMI) was recorded and body weight was measured at the beginning and end of the study. Thermography (IRT) images of the scrotum, as well as heart rate (HR), respiratory rate (RR), and rectal temperature, were taken twice daily. Separate mixed analysis of variance models were used to test the effects of treatment, time, and their interaction on mean body temperature, IRT, HR, and RR. Autoregressive covariance structure was utilized to account for repeated measures and individual goat DMI prior to the study was added as a covariate. There were no differences in vital parameters, IRT measurements, cortisol, or PGE2 in animals receiving either TD FM or placebo following castration ( P > 0.05). DMI had a treatment by hour interaction and was significantly higher in FM CAST and SHAM groups than the PL CAST group ( P = 0.04). Goats in the SHAM group gained weight throughout the study, whereas goats in all other groups lost weight ( P = 0.02). Results indicate that TD FM may mitigate pain as demonstrated by increased DMI; however, a single dose may not be sufficient to reduce physiological indicators of pain associated with castration in goats.